Nativity, Country of Education, and Mexican-Origin Women’s Breastfeeding Behaviors in the First 10 Months Postpartum - Hendrick, C. Emily (Birth, 2016)
BACKGROUND: Breastfeeding is associated with numerous health benefits for the infant and mother. Latina women in the U.S. have historically had high overall rates of initiation and duration of breastfeeding. However, these rates vary by nativity and time lived in the U.S. Exclusive breastfeeding patterns among Latina women are unclear. In this study we investigate the current and exclusive breastfeeding patterns of Mexican-origin women at four time points from delivery to 10 months postpartum to determine the combined association of nativity and country of education with breastfeeding duration and supplementation. METHODS: Data are from the Postpartum Contraception Study, a prospective cohort study of postpartum women ages 18–44 recruited from three hospitals in Austin and El Paso, TX. We included Mexican-origin women who were born in either the U.S. or Mexico in the analytic sample (n=593). RESULTS: Women completing schooling in Mexico had higher rates of overall breastfeeding throughout the study period than women educated in the U.S., regardless of country of birth. This trend held in multivariate models while diminishing over time. Women born in Mexico who completed their schooling in the U.S. were least likely to exclusively breastfeed. DISCUSSION: Country of education should also be considered when assessing Latina women’s risk for breastfeeding discontinuation. Efforts should be made to identify the barriers and facilitators to breastfeeding among U.S.-educated Mexican-origin women to enhance existing breastfeeding promotion efforts in the U.S.